Impact of high-intensity interval training on cardiac structure and function after COVID-19: an investigator-blinded randomized controlled trial - Rasmussen, I. E.; Løk, M.; Durrer, C. G.; Foged, F.; Schelde, V. G.; Budde, J. B.; Rasmussen, R. S.; Høvighoff, E. F.; Rasmussen, V.; Lyngbæk, M.; Jønck, S.; Krogh-Madsen, R.; et al. (Journal of Applied Physiology, 2023)
A large proportion of patients suffer from a persistent reduction in cardiorespiratory fitness after recovery from COVID-19, of which the effects on the heart may potentially be reversed through the effect of high-intensity interval training (HIIT). In the present study, we hypothesized that HIIT would increase left ventricular mass (LVM) and improve functional status and health-related quality of life (HRQoL) in individuals previously hospitalized for COVID-19. In this investigator-blinded, randomized controlled trial, 12 wk of supervised HIIT (4 × 4 min, three times a week) was compared with standard care (control) in individuals recently discharged from hospital due to COVID-19. LVM was assessed by cardiac magnetic resonance imaging (cMRI, primary outcome), whereas the pulmonary diffusing capacity (DLCOc, secondary outcome) was examined by the single-breath method. Functional status and HRQoL were assessed by Post-COVID-19 functional scale (PCFS) and King`s brief interstitial lung disease (KBILD) questionnaire, respectively. A total of 28 participants were included (age 57 ± 10, 9 females; HIIT: 58 ± 11, 4 females; standard care: 57 ± 9, 5 females), LVM increased in the HIIT vs. standard care group with a between-group difference of 6.8 [mean, 95%CI: 0.8; 12.8] g; P = 0.029. There were no between-group differences in DLCOc or any other lung function metric, which gradually resolved in both groups. Descriptively, PCFS suggested fewer functional limitations in the HIIT group. KBILD improved similarly in the two groups. HIIT is an efficacious exercise intervention for increasing LVM in individuals previously hospitalized for COVID-19.